Characteristic redshift and intensity enhancement as far-IR fingerprints of the halogen bond involving aromatic donors. Issue 13 (3rd February 2016) - Vasylyeva, Vera; Catalano, Luca; Nervi, Carlo; Gobetto, Roberto; Metrangolo, Pierangelo; Resnati, Giuseppe
Abstract : Characteristic redshift and intensity enhancement of the C–I stretching band have been proven to be distinct signatures of the halogen bond involving iodopentafluorobenzene. Abstract : Six halogen-bonded cocrystals involving aromatic donors have been studied by far-IR spectroscopy. Characteristic redshift and intensity enhancement of the C–I stretching band have been observed, which provided a distinct signature of the halogen bond involving iodopentafluorobenzene.